Elevated expression of CX3C chemokine receptor 1 mediates recruitment of T cells into bone marrow of patients with acquired aplastic anaemia. (5th March 2014) - Ren, J.; Hou, X. Y.; Ma, S. H.; Zhang, F. K.; Zhen, J. H.; Sun, L.; Sun, Y. X.; Hao, Y. L.; Cheng, Y. F.; Hou, M.; Xu, C. G.; Zhang, M. H.; et al.
Abstract: Objective: Acquired aplastic anaemia (AA) is a T‐cell‐mediated, organ‐specific autoimmune disease characterized by haematopoietic stem cell destruction in the bone marrow. The exact molecular mechanism of T‐cell trafficking into the bone marrow is unclear in AA. Very late activation antigen‐4 (VLA‐4) and CX3C chemokine receptor 1 (CX3CR1) play active roles in many autoimmune diseases. Therefore, we investigated whether VLA‐4 and CX3CR1 also contribute to T‐cell migration into the bone marrow in acquired AA. Design, setting and subjects: Expression levels of CX3CR1 and VLA‐4 and their ligands [fractalkine (CX3CL1) and vascular cell adhesion molecule‐1 (VCAM‐1)] were examined in 63 patients with AA and 21 healthy control subjects. T‐cell chemotaxis and adhesion were analysed in 17 patients with severe AA. We also prospectively evaluated the expression pattern of CX3CR1 during treatment with antithymocyte globulin plus cyclosporine in 11 patients with severe AA. Results: The proportion of peripheral and bone marrow CD4 + and CD8 + T cells expressing CX3CR1 and the level of CX3CL1 was increased in patients with AA. However, there was no significant difference in VLA‐4 expression or VCAM‐1 levels. Functional studies demonstrated that chemotaxis towards autologous bone marrow plasma or soluble CX3CL1 was significantly higher in T cells from AA patients and could be blocked by CX3CR1 inhibitors. CX3CR1‐mediated T‐cell adhesion was also upregulated in these patients. The expression of CX3CR1 was associated with the efficacy of immunosuppressive therapy. Conclusion: The present findings demonstrate that CX3CR1 plays a pivotal role in recruitment of T cells into the bone marrow in acquired AA and is a potential therapeutic target for treatment of this disorder.